A Successful Pregnancy in Women with Uterine Didelphys - Khadka, Sailaja; Lama, Poonam (Nepal Journal of Obstetrics and Gynaecology, 2018)
We report a didelphys uterus in 36 years female diagnosed intra-operatively who underwent Cesarean Section for fetal distress. The fetus was found in one uterus while another uterus was empty.